How Well Communication Works in Academic Supervision - Mahatika, Anis; Asmendri, Asmendri (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study discussed how well communication worked during academic supervision at MAN 2 Tanah Datar. This research used a qualitative phenomenological method. The data were collected by using unstructured interviews, observations, and documentation studies. Then the informants were chosen by snowball sampling technique. The data analysis by Miles and Huberman model techniques was used in this study, which consisted of data reduction, data presentation, and conclusion drawing and verification. Meanwhile, the researchers used data triangulation techniques to test the validity of the data. The results of the study showed that to create effective communication during academic supervision, supervisors must have communication skills such as: 1) respecting the supervised teachers; 2) having empathy, that means prioritizing to listen, understand and feel what the teacher feels; 3) being audible, that means that the teacher can properly accept the supervisor’s instruction; 4) giving clear instruction to the teachers; and 5) being friendly and wise in supervising the teacher.